Effective Bandgap Engineering in Perovskite Ferroelectrics by Successive Multiple Doping. Issue 1 (20th September 2019) - Samanta, Shibnath; Rath, Martando; Sankaranarayanan, Venkataraman; Sethupathi, Kanikrishnan; Rao, M. S. Ramachandra
Abstract : A very effective method of bandgap engineering in perovskite ferroelectrics by successive multiple doping (SMD) is proposed, tested, and compared with conventional incremental solitary doping (ISD). The application of SMD of La, Nb, and Fe (2% each) in Pb(Zr, Ti)O3 (PZT) tailors the bandgap to 2.74 from 3.53 eV (bandgap of pure PZT). This finds potential applications in ferroelectrics‐based photovoltaics and optoelectronics. In contrast, only La doping even up to 10% curtails the bandgap to 3.10 eV. The X‐ray photoelectron spectroscopy study confirms the presence of all elements doped and their chemical states. Analysis of photoluminescence shows that the emissions corresponding to the incorporations of La, Nb, and Fe are in the forbidden region of the energy band. In the case of only La doping, the emission corresponding to La gets broadened as its concentration increases. These observations are summarized and the mechanism of a larger bandgap reduction by SMD compared with solitary doping is explained in a systematic way. Comparing the ferroelectric hysteresis, true switchable polarization, and fatigue behaviors, it is found that ferroelectricity is affected marginally by SMD of La, Nb, and Fe compared with that by the ISD of La up to10%. Abstract : An increment in the dopant concentration broadens the dopant‐induced defect bands. However, the addition of a second dopant adds new defect bands. Thus, the reduction in the bandgap is higher in successive multiple doping (3.53–2.74 eV for 2% of La–Nb–Fe) than conventional incremental solitary doping (3.53–3.10 eV for 10% La).